Intelligent Systems: Models and Applications Revised and Selected Papers from the 9th IEEE International Symposium on Intelligent Systems and Informatics SISY 2011 - Pap, Endre (Topics in Intelligent Engineering and Informatics, 2013)
The theory and applications of  intelligent systems is today an important field of research. This  book is an up-to-date collection of seventeen chapters, written by recognized experts in the field. In an introductory mathematical foundations part an overview of generalizations of the integral inequalities for nonadditive integrals  and a construction of the General Prioritized Fuzzy Satisfaction Problem is given. Then different aspects of robotics are presented, such as the differences between human beings and robots, the  motion of bipedal humanoid robots, and an evaluation of  different autonomous quadrotor flight controllers. Also Fuzzy Systems are presented by a model of basic planar imprecise geometric objects  allowing  various applications in image analysis , GIS, and robotics, as well as a  type-2 fuzzy logic in  a software library for developing perceptual computers, and a two--degree--of--freedom  speed control solutions for a brushless Direct Current motor.  The book also presents recent applications in medicine such as  a Virtual Doctor System, methods for a face to face human machine interaction, and  an emotion estimation,  with applications   for multiple diseases and the effect of the applied therapy. The last part of the book covers different applications in transportation, network monitoring, and localization of pedestrians in images.